Development of stereo vision in young infants. (2nd August 2020) - Röthlisberger, Martina; Frick, Andrea
Abstract: In this study, infants' visual processing of depth‐inducing stimuli was tested using a new method suitable for experimental settings. Stereograms of the Lang‐Stereopad ® were presented in a timed preferential‐looking paradigm to determine infants' preference for a stereogram as compared to a stimulus not inducing an impression of depth. A total of 80 infants were tested at 7 months of age; of these, a sub‐sample of 41 infants were tested longitudinally at 4 and 7 months to characterize the developmental trajectory of their preference. Infants were simultaneously presented with a card showing a random‐dot stereogram (800ʺ disparity) and a similar looking dummy card without stereogram. In the total sample, 7‐month‐olds showed a clear preference for the stereogram regardless of sex. In the longitudinal sample, 7‐month‐olds but not 4‐month‐olds looked significantly longer to the stereogram as compared to the dummy card. On individual level, 56% of the 4‐month‐olds and 85% of the 7‐month‐olds predominantly looked at the stereogram. The findings yield evidence for a clear developmental progression and show that the test cards of the Lang‐Stereopad ® prototype provide a viable instrument to determine the preference for depth‐inducing stimuli in young infants when used in a controlled experimental setting.